Language anxiety: its impact on english proficiency in diploma in electrical and electronics engineering (DEE) students - Norkatyniy Ismail; Hazian Ismail; Aida Fazlin Hisham (Global Econedu, 2024)
This investigation examines the phenomenon of language anxiety and its impact on the English proficiency of Diploma in Electrical and Electronics Engineering (DEE) students. The principal research goals encompass three key components: identifying the main factors that lead to language anxiety in DEE students, evaluating the correlation between language anxiety and English proficiency levels, and exploring successful approaches for alleviating language anxiety and enhancing English proficiency. Utilizing a quantitative survey method, the study pinpoints key sources of anxiety such as apprehension towards negative evaluations, communication anxiety, and test-related stress. Using SPSS version 2.0 the data was thoroughly analysed. The findings highlighted that about half of the respondents agreed to anxiety affects their English proficiency with mean value 3.07. The data shows a noteworthy inverse correlation between language anxiety and English proficiency, suggesting that heightened anxiety levels correspond to diminished proficiency. Moreover, the investigation underscores various successful approaches for alleviating language anxiety, which involve providing positive reinforcement, enhancing exposure to English in low-pressure settings, and integrating anxiety-alleviating techniques into English as a Second Language instructional practices. The results emphasize the importance of addressing language anxiety to enhance learning outcomes and propose practical steps for educators in improving English proficiency.